Behaviour of Macro Synthetic Fiber Reinforced Concrete Columns Under Concentric Axial Compression. (2015) - Rosidawani,; Imran, Iswandi; Sugiri, Saptahari; Pane, Ivindra
Abstract: Previous studies have shown that fiber reinforced concretes can improve post-peak behaviour, ductility and energy-dissipation ability of concrete elements under flexure, shear and axial load. Ductile behaviour is one of the essential characteristics that have to be possessed by structures located in moderate to high seismic regions. This paper presents an experimental investigation of a series of nine macro synthetic fiber-reinforced concrete (MSNFRC) circular columns. The objective of the studies was to investigate the effects of the macro synthetic fibers on strength and ductility of the columns. The test parameters were the spacing of the spiral reinforcement and the volume fraction of the macro synthetic fibers. In two-thirds of the specimens, when macro synthetic fibers were added to the specimens, spiral reinforcement was reduced. The remaining specimens were detailed in accordance with the code minimum requirement for spiral reinforcement in order to examine the influence of the fibers on strength and ductility. A concentric axial compression load was applied monotically on the column specimens. The results show that the addition of macro synthetic fibers leads to improved ductility and strength. Furthermore, based on this study, the code required spiral reinforcement can be reduced whenever MSNFRC is used.